Kontribusi Dinas Pendidikan dan Kebudayaan dalam Mengatasi Kekurangan Tenaga Pendidik dan Fasilitas Pendidikan Tingkat Dasar di Kabupaten Pidie - Handayani, Handayani; Musdiani, Musdiani; Rita Novita (Dinasti Research, 2024)
This research aims to describe and analyze the contribution of the Department of Education and Culture in overcoming the shortage of teaching staff and lack of basic level facilities in Pidie Regency for the period 2019 - 2024. This research uses a qualitative research approach, with the type of research being descriptive. The sample for this research was 74 elementary schools in Pidie Regency. Data collection techniques in this research used interview, observation and documentation techniques. The data analysis technique in this research uses four stages, namely data collection, data reduction, display and data verification. Research shows that the Pidie Regency Education and Culture Office for the 2019-2024 period is overcoming the shortage of basic education personnel by quickly inducting new personnel to replace retirees, increasing human resources through supervision, recruiting P3K, and using contract, honorary and community service teachers. To overcome the lack of educational facilities, they collect information on school needs, provide facilities, provide budget assistance, and monitor their use according to learning needs.